2011
DOI: 10.1175/2010jcli3475.1
|View full text |Cite
|
Sign up to set email alerts
|

Indian and Pacific Ocean Influences on Southeast Australian Drought and Soil Moisture

Abstract: The relative influences of Indian and Pacific Ocean modes of variability on Australian rainfall and soil moisture are investigated for seasonal, interannual, and decadal time scales. For the period 1900-2006, observations, reanalysis products, and hindcasts of soil moisture during the cool season (June-October) are used to assess the impacts of El Niñ o-Southern Oscillation (ENSO) and the Indian Ocean dipole (IOD) on southeastern Australia and the Murray-Darling Basin, two regions that have recently suffered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 66 publications
(113 reference statements)
13
112
0
Order By: Relevance
“…Many previous studies have linked Australian climate to various large-scale remote climate drivers (Risbey et al 2009;Ummenhofer et al 2011;Hunter and Binyamin 2012;Fierro and Leslie 2014), and most of these studies focused on rainfall variability. The El Niño-Southern Oscillation (ENSO) (Taschetto and England 2009;Cai et al 2011;Ummenhofer et al 2011), Indian Ocean Dipole (IOD) (Risbey et al 2009;Cai et al 2011), Southern Hemisphere annular mode (SAM) (Hendon et al 2007;Meneghini et al 2007;Risbey et al 2009;Feng et al 2010a), sea surface temperature (SST) in the Wharton Basin (Li et al 2012a) and monsoon-like Southwest Australian circulation (SWAC) (Feng et al 2010b(Feng et al , 2015Li et al 2011) are all reported to modulate Australian rainfall on interannual time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have linked Australian climate to various large-scale remote climate drivers (Risbey et al 2009;Ummenhofer et al 2011;Hunter and Binyamin 2012;Fierro and Leslie 2014), and most of these studies focused on rainfall variability. The El Niño-Southern Oscillation (ENSO) (Taschetto and England 2009;Cai et al 2011;Ummenhofer et al 2011), Indian Ocean Dipole (IOD) (Risbey et al 2009;Cai et al 2011), Southern Hemisphere annular mode (SAM) (Hendon et al 2007;Meneghini et al 2007;Risbey et al 2009;Feng et al 2010a), sea surface temperature (SST) in the Wharton Basin (Li et al 2012a) and monsoon-like Southwest Australian circulation (SWAC) (Feng et al 2010b(Feng et al , 2015Li et al 2011) are all reported to modulate Australian rainfall on interannual time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum rainfall occurred along the southeastern and eastern coast, as well as the northern and southwestern coast, decreasing far inland. Previous studies demonstrated that Australian spring rainfall is influenced by many factors, such as the El Niño-Southern Oscillation (ENSO) (e.g., McBride and Nicholls 1983;Ropelewski and Halpert 1987;Nicholls et al 1996;Chiew et al 1998;Taschetto and England 2009), the Indian Ocean dipole (e.g., Saji et al 1999;Ashok et al 2003;Ummenhofer et al 2011), and the Antarctic Oscillation or southern annular mode (e.g., Gong and Wang 1999;Thompson and Wallace 2000;Marshall 2003;Hendon et al 2007). For example, studies find that Australian rainfall tends to be below average during El Niño events and above average during La Niña events, especially across the eastern two-thirds of the Australian continent during austral spring (e.g., Allan 1988;Wang and Hendon 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of saturation of this sub-surface layer appears to act as a low pass filter on the catchment precipitation in a similar way to the finding of Ummenhofer et al (2011). This property could possibly be employed in future attempts to predict lake levels following periods of heavy rain.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 64%